Nsp16 shields SARS–CoV-2 from efficient MDA5 sensing and IFIT1-mediated restriction - Ruß, Alina; Wittmann, Sabine; Tsukamoto, Yuta; Herrmann, Alexandra; Deutschmann, Janina; Lagisquet, Justine; Enßer, Armin; Kato, Hiroki; Gramberg, Thomas (EMBO Reports, 2022)
Methylation of the mRNA 5′ cap by cellular methyltransferases enables efficient translation and avoids recognition by innate immune factors. Coronaviruses encode viral 2′-O-methyltransferases to shield their RNA from host factors. Here, we generate recombinant SARS–CoV-2 harboring a catalytically inactive 2′-O-methyltransferase Nsp16, Nsp16mut, and analyze viral replication in human lung epithelial cells. Although replication is only slightly attenuated, we find SARS–CoV-2 Nsp16mut to be highly immunogenic, resulting in a strongly enhanced release of type I interferon upon infection. The elevated immunogenicity of Nsp16mut is absent in cells lacking the RNA sensor MDA5. In addition, we report that Nsp16mut is highly sensitive to type I IFN treatment and demonstrate that this strong antiviral effect of type I IFN is mediated by the restriction factor IFIT1. Together, we describe a dual role for the 2′-O-methyltransferase Nsp16 during SARS–CoV-2 replication in avoiding efficient recognition by MDA5 and in shielding its RNA from interferon-induced antiviral responses, thereby identifying Nsp16 as a promising target for generating attenuated and highly immunogenic SARS–CoV-2 strains and as a potential candidate for therapeutic intervention.
CRIS-Team Scopus Importer:2022-11-04
Keywords: 2′-O-methyltransferase; IFIT1; MDA5; Nsp16; SARS–CoV-2

Propagation of SARS-CoV-2 in a Closed Cell Culture Device: Potential GMP Compatible Production Platform for Live-Attenuated Vaccine Candidates under BSL-3 Conditions? - Klessing, Stephan; Peter, Antonia Sophia; Fraedrich, Kirsten; Wagner, Jannik; Kummer, Mirko; Deutschmann, Janina; Steininger, Philipp; Steibl, Hans Dieter; Überla, Klaus (Viruses, 2023)
Live-attenuated SARS-CoV-2 vaccines present themselves as a promising approach for the induction of broad mucosal immunity. However, for initial safety assessment in clinical trials, virus production requires conditions meeting Good Manufacturing Practice (GMP) standards while maintaining biosafety level 3 (BSL-3) requirements. Since facilities providing the necessary complex ventilation systems to meet both requirements are rare, we here describe a possibility to reproducibly propagate SARS-CoV-2 in the automated, closed cell culture device CliniMACS Prodigy® in a common BSL-3 laboratory. In this proof-of-concept study, we observed an approximately 300-fold amplification of SARS-CoV-2 under serum-free conditions with high lot-to-lot consistency in the infectious titers obtained. With the possibility to increase production capacity to up to 3000 doses per run, this study outlines a potential fast-track approach for the production of live-attenuated vaccine candidates based on highly pathogenic viruses under GMP-like conditions that may contribute to pandemic preparedness.
CRIS-Team Scopus Importer:2023-03-10
Keywords: CliniMACS Prodigy®; GMP; human challenge study; live-attenuated vaccines; SARS-CoV-2; virus propagation

SAMHD1 … and Viral Ways around It. - Deutschmann, Janina; Gramberg, Thomas (Viruses, 2021)
The SAM and HD domain-containing protein 1 (SAMHD1) is a dNTP triphosphohydrolase that plays a crucial role for a variety of different cellular functions. Besides balancing intracellular dNTP concentrations, facilitating DNA damage repair, and dampening excessive immune responses, SAMHD1 has been shown to act as a major restriction factor against various virus species. In addition to its well-described activity against retroviruses such as HIV-1, SAMHD1 has been identified to reduce the infectivity of different DNA viruses such as the herpesviruses CMV and EBV, the poxvirus VACV, or the hepadnavirus HBV. While some viruses are efficiently restricted by SAMHD1, others have developed evasion mechanisms that antagonize the antiviral activity of SAMHD1. Within this review, we summarize the different cellular functions of SAMHD1 and highlight the countermeasures viruses have evolved to neutralize the restriction factor SAMHD1.
CRIS-Team WoS Importer:2021-04-09